Prosocial tendencies measure adaptation : a Portuguese contribute for the heroic imagination project - Silva, Sara Emanuela Castro Nunes da (2016)
Human strengths have been emerging as a topic of great interest, especially because they may provide us with a path to develop a more just and equal world. Psychology has paid small attention to human behavior that considers the welfare of others above it’s one (Zimbardo, 2004) and for such reason the Heroic Imagination Project has set its goal to redefine heroism making it reachable for anyone. Because we expect to implement the HIP in Portugal and evaluate the direct outcomes of the interventions, we have made the aim of the present study to develop the Portuguese version of one of the evaluation instruments that compose HIP’s evaluation protocols: the Prosocial Tendencies Measure (PTM), measuring six types of prosocial tendencies. We have used a convenience sample of 1.457 high school students. We present evidence of a validated five-factor structure (emotional / dire; anonymous; public; compliant; altruism), supporting the notion of differentiated forms of helping, as pointed out by the literature. The exploratory factor analysis demonstrates that the Portuguese version of the PTM is reliable and internally consistent, enhancing the utility of the PTM as a valid measure of prosocial behaviors to be use with late Portuguese adolescents.